Pesantren as a Base for Instilling Religious Moderation Values - Samsudin, Samsudin; Ali, Mudzakkir; Ekaningrum, Ifada Retno (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
As the oldest educational institution in Indonesia, Islamic boarding schools, famously known as Pesantren, are institutions which have persistence in transforming Islamic values. The persistence of Islamic boarding schools in affirming their role as educational institutions that always keep up with current developments is characterized by a responsive attitude to issues of religious moderation. In the global context, religious moderation is very necessary as a collective commitment to maintaining peace and national integrity. The existence of Islamic boarding schools is again being challenged to be adaptive in responding to problems of religious moderation. This research is intended to answer the problem formulation regarding what the values of religious moderation mean, what are the characteristics of Islamic boarding schools, and how to instil the values of religious moderation in Islamic boarding schools. Through a phenomenological approach and reflective logic, Islamic boarding schools' responses to the dynamics of global problems increasingly appear comprehensive. Islamic boarding schools are increasingly reaffirming their identity as educational institutions that teach tolerant attitudes, respect plurality and preach the teachings of Islam as a bringer of peace. The research results show that Islamic boarding schools are worthy of being a basis for preserving the values of religious moderation through internalizing the values of Tawassut, Tawazun, I'tidal, Tasamuh, Musawah, Shura.